2001
DOI: 10.1086/323201
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Therapy Adherence and Viral Suppression in HIV‐Infected Drug Users: Comparison of Self‐Report and Electronic Monitoring

Abstract: To compare electronically monitored (MEMS) with self-reported adherence in drug users, including the impact of adherence on HIV load, we conducted a 6-month observational study of 67 antiretroviral-experienced current and former drug users. Adherence (percentage of doses taken as prescribed) was calculated for both the day and the week preceding each of 6 research visits. Mean self-reported 1-day adherence was 79% (median, 86%), and mean self-reported 1-week adherence was 78% (median, 85%). Mean MEMS 1-day adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
417
3
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 548 publications
(451 citation statements)
references
References 25 publications
26
417
3
1
Order By: Relevance
“…Most evidence shows that medication adherence plays an important role in glycemic control, but many other factors can affect glycemic control besides medicationtaking (e.g., diet, exercise, extent of insulin deficiency, and adequacy of the prescribed regimen), so comparisons of self-report medication adherence measures to the clinical outcome of HbA1c levels should show a modest relationship at best. Expectations regarding the ability of self-report measures to predict clinical outcomes should be set accordingly [2,53] [18,51,54]. A review of type 2 diabetes research found that significant relationships between medication adherence and glycemic control occurred more frequently in studies measuring adherence via prescription refill rather than various self-report measures [18].…”
Section: Validity Of Medication Adherence Self-reportsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most evidence shows that medication adherence plays an important role in glycemic control, but many other factors can affect glycemic control besides medicationtaking (e.g., diet, exercise, extent of insulin deficiency, and adequacy of the prescribed regimen), so comparisons of self-report medication adherence measures to the clinical outcome of HbA1c levels should show a modest relationship at best. Expectations regarding the ability of self-report measures to predict clinical outcomes should be set accordingly [2,53] [18,51,54]. A review of type 2 diabetes research found that significant relationships between medication adherence and glycemic control occurred more frequently in studies measuring adherence via prescription refill rather than various self-report measures [18].…”
Section: Validity Of Medication Adherence Self-reportsmentioning
confidence: 99%
“…typically indicates that self-report measures have weaker or less consistent relations with clinical outcomes relative to other measures of adherence [18,51,54]. A review of type 2 diabetes research found that significant relationships between medication adherence and glycemic control occurred more frequently in studies measuring adherence via prescription refill rather than various self-report measures [18].…”
Section: Practice and Public Health Policiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These data are downloaded to a computer using PowerView software (Aardex Ltd.) that stores the information in a database. In this study, we monitored one selected HAART medication as the primary outcome measure of adherence, as research has shown it to be more sensitive than other methods (Arnsten et al, 2001;McNabb et al, 2003). On-time MEMS cap openings were expressed as the percentage of scheduled dosing times when the cap was opened "on-time," defined as taking place in a 4-hour window (2 hours before or after) around the scheduled dosage time, that is, percent observed openings/percent expected openings.…”
Section: Medication Adherence Measuresmentioning
confidence: 99%
“…Overall self-reported adherence was higher than MEMS [14,45,46]. However, MEMS adherence was strongly correlated with concurrent viral load [14,[47][48][49][50]. In the paper of Arnsten, the mean self-reported 1-day adherence was 79% compared to electronic monitoring (MEMS) of 52%.…”
Section: Patient Independent Drug Monitoring Techniquesmentioning
confidence: 99%